ADVANCEMENTS IN CHICKENPOX TREATMENT: EXPLORING NOVEL THERAPEUTIC METHODS - Abbasov Khojimukhammad Khabibullaevich; Rashidov Fayod Abduraufovuch; Rashidova Laziza Abduraufovna; Utayeva Nargiza Baxtiyor qizi; Kiyamov Azizbek Utkitovich (PEDAGOGS, 2024)
Chickenpox, caused by the varicella-zoster virus (VZV), is a highly contagious infectious disease primarily affecting children. While vaccination has proven effective in preventing chickenpox, breakthrough cases and the potential for complications in immunocompromised individuals persist. This scientific article reviews recent advancements in the treatment of chickenpox, exploring novel therapeutic methods that aim to reduce symptom severity, accelerate recovery, and minimize complications. The study evaluates the efficacy and safety of emerging treatments, shedding light on potential breakthroughs in managing this viral infection.